2012
DOI: 10.2486/indhealth.ms1369
|View full text |Cite
|
Sign up to set email alerts
|

Application of Local Exhaust Ventilation System and Integrated Collectors for Control of Air Pollutants in Mining Company

Abstract: Abstact: Local exhaust ventilation (LEV) systems and integrated collectors were designed and implemented in a mining company in order to control emitted air pollutant from furnaces. The LEV was designed for capture and transition of air pollutants emitted from furnaces to the integrated collectors. The integrated collectors including four high efficiency Stairmand model cyclones for control of particulate matter, a venturi scrubber for control of the fine particles, SO 2 and a part of h 2 S to follow them, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Measures for isolating wood smoke at the source were absent at all sites; thus workers probably breathed in wood smoke from the burning kilns. On the contrary, earlier studies have demonstrated that local exhaust ventilation can efficiently purify contaminated air, and its consistent application has effectively decreased workplace hazards below the threshold limit value 38 39. In addition, health and safety information is indispensable for ensuring a safe work environment and developing educational materials for workers can reduce the risk of work-related injuries;40 nevertheless, no educational material was displayed at any of the sites.…”
Section: Discussionmentioning
confidence: 99%
“…Measures for isolating wood smoke at the source were absent at all sites; thus workers probably breathed in wood smoke from the burning kilns. On the contrary, earlier studies have demonstrated that local exhaust ventilation can efficiently purify contaminated air, and its consistent application has effectively decreased workplace hazards below the threshold limit value 38 39. In addition, health and safety information is indispensable for ensuring a safe work environment and developing educational materials for workers can reduce the risk of work-related injuries;40 nevertheless, no educational material was displayed at any of the sites.…”
Section: Discussionmentioning
confidence: 99%
“…Gustav Nyrenstedt also stated that the fumes moved up the electrode and the electrode holder and therefore the suction hood could be set at any height along the electrode (Nyrenstedt, 2016). Local exhaust ventilation, according to Ghorbani Shahna et al, is one of the most effective strategies to remove contaminants from reverberatory furnaces and heated sources (Ghorbani Shahna et al, 2012). It has been found, as a result of research carried out by Memon and colleagues, that the velocity of the material is linked to the amount of heat that is generated (Memon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A hypersensitive state in the airways around the human respiratory system may attack the worker's even at low levels of polluted air exposures. The occurence occur cause by initial working conditions which are exposed to repeated and long-term exposure to polluted air [3,4]. Heavy exposure to dust, fume or other airborne contaminants in a confined space may result in acute and chronic diseases.…”
Section: Introductionmentioning
confidence: 99%